2018
DOI: 10.1108/pm-04-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting operation and maintenance cost of hotels

Abstract: Purpose The purpose of this paper is to identify, assess, rank, and compare the most influencing factors in three-, four-, and five-star hotels in the Eastern Province in Saudi Arabia. Design/methodology/approach A combination of literature and interviewing of ten local experts have resulted in the identification of 46 factors. Through a web-based questionnaire survey, the identified factors were ranked. A total of 23 responses were gathered from the full population of the 47 hotels (14 five-star, 15 four-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
0
24
0
2
Order By: Relevance
“…B. Ihsan et al, (2018) identified and grouped some of the factors into seven ( 7) categories where engineering services, labor, building materials, environments, management and administration, budget and finance, and building users are included as the factors. This was confirmed by A.S. Ali et al, (2010) and N.Z.…”
Section: 97mentioning
confidence: 99%
“…B. Ihsan et al, (2018) identified and grouped some of the factors into seven ( 7) categories where engineering services, labor, building materials, environments, management and administration, budget and finance, and building users are included as the factors. This was confirmed by A.S. Ali et al, (2010) and N.Z.…”
Section: 97mentioning
confidence: 99%
“…Barriers to the preparation of an accurate MB were defined under major variables, they are technical factors, managerial factors, financial factors, environmental factors, and social factors. According to Ihsan (2017), design problems, faulty maintenance, building characteristics, poor Quality Control, Life cycle cost techniques, low concern for future maintenance, and failure in identifying the true cause of defect were identified as technical factors. The managerial role in most commercial buildings includes organising, controlling, planning and staffing and these components are important in the performance of maintenance work and thus affect the building's maintenance costs (Schuh, Jussen and Optehostert, 2019).…”
Section: Barriers and Strategiesmentioning
confidence: 99%
“…Due to a lack of scientific procedures for evaluating the budget, subjective and erroneous allocations have resulted in waste or a shortage of resources (Srivastava, Kumar and Gupta, 2020). According to Ihsan (2017), inadequate finance and poor financial control when executing maintenance work were identified as financial factors that affect the cost of maintenance. New maintenance techniques, unqualified and unavailable maintenance contractors, insufficient standards and specifications, and harsh climatic conditions were identified as different environmental factors.…”
Section: Barriers and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers addressed the factors affecting maintenance cost such as (El-Haram and Horner 2002, Al-Khatam 2003, Lai and Yik 2008, Ali, Kamaruzzaman et al 2010, Sanjeev, Jauhari et al 2012, Hassanain, Assaf et al 2013. And limited researches tried to set a benchmark or index number for maintenance cost especially in hotel industry (Chan 2008, Róka-Madarász, Mályusz et al 2016 Planning the maintenance activities and allocating constrained budgets required to carry such operations in advance are difficult tasks for the maintenance managers (Ihsan and Alshibani 2018). So, it is necessary to identify index numbers for hotel maintenance cost rationale to the hotel capacity parameters Simple index number again can be constructed either by -(i) Simple aggregate method, or by (ii) simple average relative's method.…”
Section: Maintenance Costmentioning
confidence: 99%